Risk Factors for Kidney Disease in Type 1 Diabetes - Perkins, Bruce A. (Diabetes Care, 2019)
OBJECTIVE: In type 1 diabetes (T1D), the course of microalbuminuria is unpredictable and timing of glomerular filtration rate (GFR) loss is uncertain. Thus, there is a need to identify the risk factors associated with the development of more advanced stages of kidney disease through large, long-term systematic analysis. RESEARCH DESIGN AND METHODS: Multivariable Cox proportional hazards models assessed the association of baseline and time-dependent glycemic and nonglycemic risk factors for incident macroalbuminuria and reduced estimated GFR (eGFR; defined as <60 mL/min/1.73 m(2)) over a mean of 27 years in the Diabetes Control and Complications Trial (DCCT) cohort. RESULTS: Higher mean HbA(1c) (hazard ratio [HR] 1.969 per 1% higher level [95% CI 1.671–2.319]) and male sex (HR 2.767 [95% CI 1.951–3.923]) were the most significant factors independently associated with incident macroalbuminuria, whereas higher mean triglycerides, higher pulse, higher systolic blood pressure (BP), longer diabetes duration, higher current HbA(1c), and lower mean weight had lower magnitude associations. For incident reduced eGFR, higher mean HbA(1c) (HR 1.952 per 1% higher level [95% CI 1.714–2.223]) followed by higher mean triglycerides, older age, and higher systolic BP were the most significant factors. CONCLUSIONS: Although several risk factors associated with macroalbuminuria and reduced eGFR were identified, higher mean glycemic exposure was the strongest determinant of kidney disease among the modifiable risk factors. These findings may inform targeted clinical strategies for the frequency of screening, prevention, and treatment of kidney disease in T1D.